2023
DOI: 10.1002/ejlt.202200161
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Gallic Acid Alkyl Esters on Lipid Oxidation of Intactly Soaked Oyster Meats and Oyster Meat Homogenates during Refrigerated Storage

Abstract: In this study, the antioxidant effects of gallic acid (GA) and its alkyl esters including methyl gallate (MG), butyl gallate (BG), octyl gallate (OG), and lauryl gallate (LG) in whole oyster meats and oyster meat homogenates during cold storage are investigated. The oxidation degree of lipid is measured by peroxide value (POV), thiobarbituric acid active substances (TBARS), and polyunsaturated fatty acid (PUFA) percentage. The results show that the lipid oxidation in the two types of samples is inhibited by GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…GA contains high phenolic content and can remove a large amount of oxygen derived free radicals as phenolic compounds can neutralize and scavenge free radicals ( Das et al, 2012 ; Ramli et al, 2020 ). Also, Luo et al (2023) reported that lipid oxidation in oyster was decreased with GA due to the antioxidant properties of alkyl esters in GA. Opposite to the effect of GA, LA is known for promoting lipid oxidation as it alters the intracellular oxidation state of lipid substances ( Xu, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…GA contains high phenolic content and can remove a large amount of oxygen derived free radicals as phenolic compounds can neutralize and scavenge free radicals ( Das et al, 2012 ; Ramli et al, 2020 ). Also, Luo et al (2023) reported that lipid oxidation in oyster was decreased with GA due to the antioxidant properties of alkyl esters in GA. Opposite to the effect of GA, LA is known for promoting lipid oxidation as it alters the intracellular oxidation state of lipid substances ( Xu, 2009 ).…”
Section: Resultsmentioning
confidence: 99%